Epsilon-poly-L-lysine: Recent Advances in Biomanufacturing and Applications - Wang, Liang; Zhang, Chongyang; Zhang, Jianhua; Rao, Zhiming; Xu, Xueming; Mao, Zhonggui; Chen, Xusheng (Frontiers in Bioengineering and Biotechnology, 2021)
ε-poly-L-lysine (ε-PL) is a naturally occurring poly(amino acid) of varying polymerization degree, which possesses excellent antimicrobial activity and has been widely used in food and pharmaceutical industries. To provide new perspectives from recent advances, this review compares several conventional and advanced strategies for the discovery of wild strains and development of high-producing strains, including isolation and culture-based traditional methods as well as genome mining and directed evolution. We also summarize process engineering approaches for improving production, including optimization of environmental conditions and utilization of industrial waste. Then, efficient downstream purification methods are described, including their drawbacks, followed by the brief introductions of proposed antimicrobial mechanisms of ε-PL and its recent applications. Finally, we discuss persistent challenges and future perspectives for the commercialization of ε-PL.